Simulation of Adhesive Joints by Viscoelastic Interface Material Model1. Issue 9 (6th August 2013) - Konchakova, Natalia; Müller, Ralf; Steinmann, Paul; Balle, Frank; Eifler, Dietmar; Barth, Franz‐Josef
<x xml:space="preserve">Abstract</x> Numerical results of lightweight metal/carbon fiber reinforced polymer (CFRP) overlapped structures modeling with different non‐elastic interfaces are presented. The hybrid joints of metal and polymer composite can be produced by ultrasonic metal welding or by means of adhesive bonding. The simulation of both types of joints is the focus of this investigation. The difference in the numerical models of the ultrasonic welded and adhesively bonded specimens is elaborated. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>